Pengaruh Shift Kerja, Stres Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Di PT. Liku Telaga Gresik - Yani Elviani Lestari; Moh. Bukhori; Fathorrahman (RELASI : JURNAL EKONOMI, 2020)
In determining and achieving a goal in a organization, one element that’s needed is human resource. In facing challenges to achieve organizational goals, continues improvement is needed to improve and enhance employee performance. The goals of this research is : 1. To know and analyze the impact of shift system to employee’s performance, 2. To know and analyze the impact of employee’s stress level to employee’s performance, 3. To know and analyze the impact of work environment to employee’s performance, 4. To know and analyze the impact of shift system, employee’s stress level, and work environment simultaneously to employee’s performance. This research is associative casual research using quantitative approach. This research was conducted on PT Liku Telaga’s employees. The population of this research is all permanent employees of PT Liku Telaga. Samples were taken using proportional random sampling method from 68 respondents. Those data were processed using SPSS software ver.20. The result of this research shows that 1. Shift system doesn’t affect significantly and affect positively to employee’s performance 2. Employee’s stress level affect significantly and affect negatively to employee’s performance 3. Work environment affect significantly and affect positively to employee’s performance 4. Shift system, employee’s stress level and work environment affect significantly to PT Liku Telaga employee’s performance.